Pentingnya Sistem Keamanan Database Untuk Melindungi Data Pribadi - Ujung, Adelia Marwah; Nasution, Muhammad Irwan Padli (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
This research is conducted with the aim of database security and protecting users' personal information. The study focuses on the database security system, which is an essential aspect in the field of information technology. The research is carried out by conducting a literature review and case studies on various existing database security systems. The fundamental concepts of the database security system, types of database security systems, and the latest technologies that can be used to enhance database security are explained in this research. Furthermore, the potential risks that can arise when the database security system is not properly maintained and strategies to address database security issues are also discussed. This research is expected to provide a better understanding of the importance of maintaining database security for organizations and companies.